Evaluasi Penerimaan End-User terhadap Aplikasi University Customer Care Center (UC3) Universitas Jember dengan Menggunakan Pendekatan Unified Theory of Acceptance and Use of Technology (UTAUT) - Mitha Ariska; Diah Ayu Retnani Wulandari; Qurrota A’yuni Ar Ruhimat (Faculty of Computer Science, University of Jember, 2019)
University Customer Care Center (UC3) is a complaint service system for active academic civitas of the University of Jember. Implementation of UC3 is expected to optimize complaints complaint related to performance evaluation at the University of Jember. One of the keys to the successful implementation of information technology, The purpose of the study is to know the factors that influence the acceptance of the academic civitas in using the UC3 application. This research will use the Unified Theory of Acceptance and Use of Technology (UTAUT) method by utilizing the Performance Expectancy (PE) variable, Effort Expectancy (EE), Social Influence (SI), and Facilitating Condition (FC) to see how it affects the intensity of application usage UC3 And the influence of moderator variables (Age and Experience) to the relationships of those variables. Based on the results of data analysis PLS-SEM known that the PE, EE, and SI variables have a positive and significant effect on the Behavioral Intention (BI) variables as well as the FC and BI variables significantly positive and significant to the Use Behavior (UB) variables. Age influences inter-variable relationships for ages 26-35 years, 36-45 years, and >45 years, while Experience influences the relationship between variables for usage intensity ≥3 times. Based on the results of the five hypotheses received can be interpreted that the UC3 application was accepted by the academic and the acceptance is still not fully.